2013
DOI: 10.1016/j.tics.2013.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Representational geometry: integrating cognition, computation, and the brain

Abstract: HighlightsRepresentational geometry is a framework that enables us to relate brain, computation, and cognition.Representations in brains and models can be characterized by representational distance matrices.Distance matrices can be readily compared to test computational models.We review recent insights into perception, cognition, memory, and action and discuss current challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
879
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 820 publications
(928 citation statements)
references
References 104 publications
4
879
0
2
Order By: Relevance
“…We used a representational similarity analysis approach, which uses the neural pattern similarity between pairs of stimuli to infer the representational similarity (22). This method is therefore wellsuited for assessing neural overlap between semantic representations (23)(24)(25), as the degree of overlap should be directly reflected in the representational similarity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a representational similarity analysis approach, which uses the neural pattern similarity between pairs of stimuli to infer the representational similarity (22). This method is therefore wellsuited for assessing neural overlap between semantic representations (23)(24)(25), as the degree of overlap should be directly reflected in the representational similarity.…”
Section: Resultsmentioning
confidence: 99%
“…We used a searchlight representational similarity analysis (22,28) to search for brain regions containing the predicted neural code. Representational similarity analysis uses the neural pattern similarity between pairs of stimuli to infer the representational similarity.…”
Section: Methodsmentioning
confidence: 99%
“…7A). The use of such approaches within neuroimaging is growing, with development and application of techniques such as representational similarity analysis (RSA) [Kriegeskorte and Kievit, 2013], and the use of supervised classification algorithms together with cross‐validation [Hastie et al, 2001], often referred to as a decoding [Haxby et al, 2014; King and Dehaene, 2014; Quian Quiroga and Panzeri, 2009]. Our new GCMI estimator allows us to address these issues within the unified framework of information theory.…”
Section: Discussionmentioning
confidence: 99%
“…Using multivariate pattern classification (Carlson et al, 2013;Cichy et al, 2014;Isik et al, 2014) and representational similarity analysis (Kriegeskorte, 2008;Kriegeskorte and Kievit, 2013;Cichy et al, 2014) on millisecond-resolved magnetoencephalography data (MEG), we identified a marker of scene size around 250 ms, preceded by and distinct from an early signal for lower-level visual analysis of scene images at ~100ms. Furthermore, we demonstrated that the scene size marker was independent of both low-level image features (i.e.…”
Section: The Temporal Dynamics Of Spatial Layout Processingmentioning
confidence: 99%